In vitro digestion of emulsions: high spatiotemporal resolution using synchrotron SAXS1. Issue 26 (14th July 2015) - Marze, Sébastien; Gaillard, Cédric; Roblin, Pierre
<x xml:space="preserve">Abstract</x> The assemblies formed during in vitro intestinal digestion of triglyceride emulsions were monitored using time-resolved synchrotron SAXS.